Characterization of the Canberra BE5030 Broad Energy High Purity Germanium Detector by means of the GEANT4 Monte Carlo simulation package - Georgali, Efstathia; et al., ... (HNPS Advances in Nuclear Physics, 2020)
The accurate determination of the efficiency of HPGe detectors is a challenging procedure due to possible self-attenuation phenomenaand/or coincidence summing effects. Both of these phenomena become important when close detection geometries and extended samples are considered. To deal with these features the simulation of HPGe detectors is used so as to calculate the corresponding correction factors, especially for those cases where low energy γ-ray are considered. Through the present work the Canberra BE5030 Broad Energy HPGe detector of the Enviromental Radioactivity Monitoring Department of Greek Atomic Energy Comission was simulated through the GEANT4 toolkit. Experimental efficiency and counting rate data were compared with the simulation results for different geometries of the detector so as to idetify the one for which the experimental data are better reproduced.